Unconditionally reliable and secure message transmission in undirected synchronous networks: possibility, feasibility and optimality. (31st January 2011) - Patra, Arpita; Choudhury, Ashish; Pandu Rangan, C.; Srinathan, Kannan
We study the interplay of network connectivity and the issues related to the 'possibility', 'feasibility' and 'optimality' for unconditionally reliable message transmission (URMT) and unconditionally secure message transmission (USMT) in an undirected synchronous network, under the influence of an adaptive mixed adversary having unbounded computing power, who can corrupt some of the nodes in the network in Byzantine, omission, fail-stop and passive fashion respectively. We consider two types of adversary, namely threshold and non-threshold. One of the important conclusions we arrive at from our study is that allowing a negligible error probability significantly helps in the 'possibility', 'feasibility' and 'optimality' of both reliable and secure message transmission protocols. To design our protocols, we propose several new techniques which are of independent interest.